PENGOLAHAN LEMAK TENGKAWANG DENGAN CARA PENGEMPAAN HIDRAULIK - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Observations in this research were conducted in the IIIipe fat industry and in the laboratory. The observation in the fat industry was to get a clear discription of the fat processing of IIIipe nut, whilts in the laboratory was to study the extraction process of IIIipe fat with a hydraulic pressing technique. The pressure were conducted at several pressing levels: 25, 50, and 75 kg/cm2, at a pressing temperature of 50-60 oC for 20 minutes respectively.To produce IIIipe fats, the industry applies a combination technique of hydraulic pressure and hexane extraction. The yield of fat with this combination technique is around 40-50 %. However, the results of experiment in the laboratory showed that at an 50 kg/cm2 pressure produced yield of fat with a high quality indicated by the highest value of iodine number.